CO2 exchange, dry matter accumulation and growth response of sorghum (Sorghum bicolor L. Moench) to terminal drought as affected by potassium and blended‐NPSBZn fertilization. (27th March 2021) - Endris, Solomon; Fetene, Masresha; Amede, Tilahun
Abstract: Sorghum production is constrained by terminal drought stress in semi‐arid areas of north‐eastern Ethiopia. Data from field experiments conducted in the region for two consecutive years (2015 – 2016) were used to investigate the effect of potassium (K) and NPSBZn‐blended fertilizer (BF) inputs on the drought response of sorghum through analysis of gas exchange, dry matter accumulation and growth parameters. Leaf gas exchange properties varied strongly with K and BF application both under normal rainfall and drought conditions. Data taken at anthesis in drought‐exposed sorghum indicated reduction of net photosynthetic rate (AN ) with BF supply. AN declined from 15.7 µmol CO2 /m 2 /s in the control to 13.4 µmol CO2 /m 2 /s with application of 164 kg/ha BF. However, higher total dry matter yield was recorded at maturity in response to blended fertilizer and K inputs. Increasing supply of NPSBZn‐blended fertilizer was associated with declining leaf K content, increasing intercellular CO2 concentration and water use efficiency (WUE) during anthesis. Significant variations in crop growth rates were also observed in response to K and BF inputs. At physiological maturity, net assimilation rate (NAR) increased with K and BF inputs both under drought and normal rainfall conditions. In general, K application modulated the response of sorghum to BF input under both normal rainfall and drought conditions. Therefore, grain sorghum could benefit from early supply of K and BF fertilizer in drought prone areas of Northeastern Ethiopia.